2008
DOI: 10.1126/science.1153633
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Saturn's South Polar Vortex

Abstract: The camera onboard the Cassini spacecraft has allowed us to observe many of Saturn's cloud features. We present observations of Saturn's south polar vortex (SPV) showing that it shares some properties with terrestrial hurricanes: cyclonic circulation, warm central region (the eye) surrounded by a ring of high clouds (the eye wall), and convective clouds outside the eye. The polar location and the absence of an ocean are major differences. It also shares properties with the polar vortices on Venus, such as pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 4 publications
1
57
1
Order By: Relevance
“…The north polar cyclone together with its southern counterpart (Dyudina et al, 2008) are the first two polar cyclonic features discovered in the giant atmospheres of the outer solar system. Cyclones exist at both poles of Venus (e.g., Suomi and Limaye, 1978;Limaye, 2007;Limaye et al, 2009), and polar vortices have been observed on Mars and Earth as well.…”
Section: Dynamical Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The north polar cyclone together with its southern counterpart (Dyudina et al, 2008) are the first two polar cyclonic features discovered in the giant atmospheres of the outer solar system. Cyclones exist at both poles of Venus (e.g., Suomi and Limaye, 1978;Limaye, 2007;Limaye et al, 2009), and polar vortices have been observed on Mars and Earth as well.…”
Section: Dynamical Implications and Conclusionmentioning
confidence: 99%
“…and maintaining the hexagon. As well, although a cyclonic hot vortex has been demonstrated to exist at the north pole in the upper troposphere and stratosphere by thermal-IR imaging , it is not known whether the vortex demonstrates cloud morphologies and wind speeds similar to the south polar cyclone (Dyudina et al, 2008(Dyudina et al, , 2009). …”
Section: Introductionmentioning
confidence: 95%
“…Analysis of thermal emissivity indicated that these structures are deep, spanning several density scale heights from the middle stratosphere down into the troposphere. Their intensity and cloud structure has prompted analogies with terrestrial hurricanes (Dyudina et al 2008(Dyudina et al , 2009. Convective processes in the atmosphere beneath the cyclones may provide a possible forcing mechanism for their maintenance, although a detailed dynamical picture of the cyclones remains beyond the reach of current observations.…”
Section: Introductionmentioning
confidence: 97%
“…We will show in this paper that this large Saturn cyclone has remained active and with few changes for at least 4 years, becoming the longest-lived cyclone ever observed in the atmospheres of Jupiter or Saturn (we do not consider here Saturn's South Polar cyclone which is in a different dynamical regime; Sánchez-Lavega et al, 2006;Dyudina et al, 2008Dyudina et al, , 2009). During the time period covered by our survey there was no other structure of comparable size at its latitude.…”
Section: Introductionmentioning
confidence: 97%